Smart Monitoring of Garbage using LoRa - Mohit Khandelwal,Hemeshwar Konduru, Akash Shetty, Kushal K A, Dr. P. I. Basarkod (International Journal of Advanced Science and Technology, 2020)
Metropolitan cities produces large amount of waste due to rapid growth in population. Most of the developing countries are lacking in proper management of waste. Due to this Garbage bins are often over filled and not emptied on time which not only results in unhygienic environment but also causes dreadful diseases. If the garbage in the bins is collected periodically, surroundings can be maintained clean and hygienic. To overcome this, we can monitor the level of garbage filled in the bins using an ultrasonic sensor. The data obtained from ultrasonic sensor can be sent through LoRa technology to the Municipal corporation. Then the Garbage truck drivers can be notified whenever the bins are full so that they can empty the filled bins. Hence the garbage in the cities can be managed periodically.